A Dose-finding Study of a Wild-type Influenza A(H3N2) Virus in a Healthy Volunteer Human Challenge Model. (16th February 2019) - Han, Alison; Czajkowski, Lindsay M; Donaldson, Amanda; Baus, Holly Ann; Reed, Susan M; Athota, Rani S; Bristol, Tyler; Rosas, Luz Angela; Cervantes-Medina, Adriana; Taubenberger, Jeffery K; Memoli, Matthew J
Abstract: Background: The development of vaccines and therapeutics has relied on healthy volunteer influenza challenge studies. A validated human infection model with wild-type A(H1N1)pdm09 was reported previously. Our objective was to characterize a wild-type influenza A/Bethesda/MM1/H3N2 challenge virus in healthy volunteers. Methods: Participants received a single dose of a cell-based, reverse-genetics, Good Manufacturing Practices–produced wild-type influenza A(H3N2)2011 virus intranasally and were isolated at the National Institutes of Health Clinical Center for ≥9 days. Dose escalation was performed from 10 4 to 10 7 TCID50 (50% tissue culture infectious dose). Viral shedding and clinical disease were evaluated daily. Results: Of 37 participants challenged, 16 (43%) had viral shedding and 27 (73%) developed symptoms, with 12 (32%) participants experiencing mild to moderate influenza disease (MMID), defined as shedding and symptoms. Only participants receiving 10 6 and 10 7 TCID50 experienced MMID at 44% and 40%, respectively. Symptom severity peaked on day 3, whereas most viral shedding occurred 1–2 days after challenge. Only 10 (29%) participants had a ≥4-fold rise in hemagglutination inhibition antibody titer after challenge. Conclusions: The A/Bethesda/MM1/H3N2 challenge virus safely induced MMID in healthy volunteers, but caused less MMID than the A(H1N1)pdm09 challenge virus even at the highest dose. There was less detection of shedding though the incidence of symptoms was similar to A(H1N1)pdm09. Fewer serum anti-hemagglutinin (HA) antibody responses with less MMID indicate that preexisting immunity factors other than anti-HA antibody may limit shedding in healthy volunteers. This A/Bethesda/MM1/H3N2 challenge virus can be utilized in future studies to further explore pathogenesis and immunity and to evaluate vaccine candidates. Clinical Trials Registration: NCT02594189 Abstract : We successfully characterized an influenza A/Bethesda/MM1/H3N2 challenge virus and show that it can be administered safely to induce mild to moderate influenza disease.